Removal of disinfection by-product precursors by coagulation and an innovative suspended ion exchange process. (15th December 2015) - Metcalfe, David; Rockey, Chris; Jefferson, Bruce; Judd, Simon; Jarvis, Peter
Abstract: This investigation aimed to compare the disinfection by-product formation potentials (DBPFPs) of three UK surface waters (1 upland reservoir and 2 lowland rivers) with differing characteristics treated by (a) a full scale conventional process and (b) pilot scale processes using a novel suspended ion exchange (SIX) process and inline coagulation (ILCA) followed by ceramic membrane filtration (CMF). Liquid chromatography-organic carbon detection analysis highlighted clear differences between the organic fractions removed by coagulation and suspended ion exchange. Pretreatments which combined SIX and coagulation resulted in significant reductions in dissolved organic carbon (DOC), UV absorbance (UVA), trihalomethane and haloacetic acid formation potential (THMFP, HAAFP), in comparison with the SIX or coagulation process alone. Further experiments showed that in addition to greater overall DOC removal, the processes also reduced the concentration of brominated DBPs and selectively removed organic compounds with high DBPFP. The SIX/ILCA/CMF process resulted in additional removals of DOC, UVA, THMFP, HAAFP and brominated DBPs of 50, 62, 62, 62% and 47% respectively compared with conventional treatment. Graphical abstract: Highlights: Coagulation modified by a new suspended ion-exchange process was investigated. Disinfection by-product (DBP) reductions were improved using the ion-exchange process. Ion-exchange and coagulation removed complimentary organic materials. A linear correlation was found between DBP concentration and specific reactivity reductions.